Evaluation of Spray Drift from an Electric Boom Sprayer: Impact of Boom Height and Nozzle Type - Xiaoyong Pan; Shuo Yang; Yuanyuan Gao; Zhichong Wang; Changyuan Zhai; Wei Qiu (Agronomy)
In the Huang-Huai-Hai region of China, the instability of electric boom sprayers has prompted many farmers to raise the boom height to improve clearance. However, the drift risks associated with these conditions remain poorly assessed. This study investigated two key factors influencing drift: boom height and nozzle type. The standard LI CHENG VP11003 nozzle was compared to the Teejet XR11003 nozzle, and droplet size and velocity were measured at various boom heights. The results showed that, at the same boom height, the LI CHENG nozzle produced droplets with an average D[V, 0.5] 14.6 µm larger (8.13%), an average velocity 0.53 m/s lower (29.26%), and a relative span (RS) value 0.05 higher (4.52%) compared to the Teejet nozzle. Drift tests were performed under field conditions using a spray drift test bench. The results showed that the total drift amount per unit area (TDA) for the LI CHENG nozzle showed minimal variation at boom heights of 0.4–0.6 m (Stage 1), 0.7–0.9 m (Stage 2), and 1.0–1.2 m (Stage 3). The drift potential of the LI CHENG VP11003 nozzle increased by 136.62% in Stage 2 and 282.69% in Stage 3, relative to Stage 1. Similarly, the Teejet XR11003 nozzle showed increases of 30.52% and 165.51% in Stages 2 and 3, respectively. The results showed that the LICHENG nozzle, which is the standard equipment on the sprayer, can only be used to moderately increase the boom height to improve the sprayer’s clearance within the range of the first stage. When the boom height exceeds this range, the drift risk becomes too high. This study provides meaningful insights into enhancing drift control and developing application strategies for growers.